PENGARUH LEG BOUND TERHADAP KEMAMPUAN LAY UP SHOOT PERMAINAN BOLA BASKET TEAM BAU-BAU - Agusta Gugun Praja; Asmuddin; Abdul Saman (Universitas Halu Oleo, 2022)
The purpose of this study was to determine the effect of leg bound training on the ability to lay up shoot in the basketball game Team Bau-Bau. This research method uses an experimental method through a quantitative approach which is carried out in a structured manner regarding data descriptions and training methods. This research design uses one group pretest-posttest design. The population in this study were all members of the Team Bau-Bau, totaling 30 people. After being selected based on the criteria set by the researcher, a sample of 20 people was obtained using purposive sampling technique. In this study, the instrument used was a lay up shoot ability test. From the results of the data obtained using the statistical technique of the T test, the value of t count = 8.132 > t table (19:19) = 2.093, at a significant level of 0.05. it can be concluded that there is a significant effect of leg bound training on the ability to shoot lay-up in the basketball game Team Bau-Bau